ANALYSIS OF THE EFFECT OF TPF, CAR, NPL, AND INFLATION AND BI RATE ON LOAN DISTRIBUTION: (Empirical Study on Commercial Banks Listed on the Indonesia Stock Exchange for the Period 2017-2019) - Azizah, Siti Nur; Apriliani , Winda; Budi Santoso, Suryo; Hapsari, Ira (International Journal Accounting Tax and Business, 2021)
Purpose – The purpose of this study was to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), inflation, and the BI rate. Design/methodology/approach – The type of data used in this study is secondary data for commercial banks in Indonesia in 2017-2019 which includes Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), inflation and BI rate. Sampling in this studywas determined using purposive sampling technique. The population in this study were 44 commercial banks listed on the Indonesia Stock Exchange (BEI) from 2017-2019. This study uses multiple linear regression analysis with the SPSS application Findings– This study has several finding, Capital Adequecy Ratio (CAR) has a negative effect on lending ,Non Performing Loan has a negative effect on lending, Inflation has a negative effect on lending, The bi rate has no effect on lending Reseach limitations/implications – This study has several limitations, namely This study only uses data from 2017-2019 so the data obtained by researchers is still limited.